(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to evaluate MPV (Mean Platelet Volume), NLR (Neutrophil-to-lymphocyte ratio), and PDW (Platelet Distribution Width) values obtained from complete blood count in patients with fibromyalgia syndrome (FMS). In addition, we aimed to investigate the relationship of these parameters with clinical conditions such as disease activity and depression.Materials and Methods: 91 patients who presented to Gaziantep University Physical Medicine and Rehabilitation department between November 2017 and March 2018 and were diagnosed with FMS according to the 2010 ACR (American Colleague of Rheumatology) criteria, and 33 healthy volunteers were enrolled in this study. Both groups filled out Fibromyalgia Impact Questionnaire (FIQ) and Hamilton Depression Rating Scale (HAM-D). Neutrophil, platelet, lymphocyte count, MPV, and PDW values were recorded from full blood count.Results: Although NLR was higher in the patient group, there was no statistically significant difference (p>0.05). While MPV and CRP values were significantly high, PDW values were significantly low in the patient group (p0.05). As the mean age values of both groups were different, a significant difference was found between the groups in terms of NLR values according to the results of regression model adjusted to age (p0.05).Conclusion: In our study, we found the NLR and MPV values to be high and the PDW values to be low, and found the NLR values to be associated with depression. The results of this study show that blood parameters can be used in FMS patients.Keywords: Inflammation; depression; fibromyalgia.